A comprehensive experimental study on heavy metal ion sensing performance of ZnPc and its electrospun nanofibers - Omur, Birsel Can; Can, Nursel; Altindal, Ahmet (SPRINGER, 2026)
The interactions of various heavy metal ions (HMIs) including Cu2+, Fe2+, Zn2+, and Cr3+ with zinc phthalocyanine (ZnPc) thin film and electrospun nanofibers (nZnPc) in aqueous solutions were comparatively investigated by using quartz crystal microbalance (QCM) technique, giving the order of maximum sensitivity S-Fe(2+) > S-Cu(2+) > S-Zn(2+) > S-Cr(3+) for ZnPc, while for the nZnPc-based sensor was S-Zn(2+) > S-Cr(3+) > S-Fe(2+) > S-Cu(2+). Formation of the ZnPc nanofibers was investigated by scanning electron microscopy (SEM) images, and these analyses showed that PVA/ZnPc composite nanofibers were successfully produced. QCM results have shown that ZnPc and nZnPc-based sensors are very promising materials for the sensing of the HMIs in water with a response time of 2 s. Limit of detection (LoD) calculations also showed that ZnPc and nZnPc have great potential for the detection of Cu2+ ions, with the LoD values of 0.14 and 0.19 ppm, respectively. HMI adsorption data were analyzed using Langmuir, Freundlich, and Temkin models, and it was found that the Freundlich model was the most suitable isotherm to represent HMI adsorption onto ZnPc and nZnPc, except for the adsorption of Fe2+ ions on the nZnPc surface.
Keywords: ADSORPTION; CHEMOSENSOR; ISOTHERMS; SORPTION; Engineering; Materials Science; Physics